Selection of the railroad container terminal in Serbia based on multi criteria decision making methods - Milosavljević, Milan; Bursać, Marko; Tričković, Goran (Decision Making: Applications in Management and Engineering, 2018)
Intermodal transport is one of the key elements for sustainable freight transport at large and medium distances. However, its efficiency in many cases depends on the location of the railroad container terminals (CT). The favorable position of Serbia provides an opportunity to establish a large number of container trains, which can lead to a more developed intermodal transport system in the entire Balkans and beyond. In this paper the problem of the container terminal location in Serbia has been considered and resolved. The aim of this paper is to determine the potential macro location of the CT in Serbia, which will be most suitable for different stakeholders in the transport chain. Choosing the most suitable alternative is a complex multi-criteria task. For this reason, a multi criteria decision-making model has been formulated which consists of a number of alternatives and criteria. Alternatives represent potential areas for a site, while some of the criteria are: cargo flows, infrastructure, economic development, social and transport attractiveness and environmental acceptability. For defining weights of the criteria two approaches are used, namely, the Delphi and the Entropy method. In this paper three methods of the multi criteria decision-making, namely, TOPSIS, ELECTRE and MABAC are used. By comparing the results of these three methods, an answer to the question where to locate CT will be presented. This is the first step in determining the location of the container terminal. The next phase should respond to the issue of micro location of the terminal. Also, after certain customization, the model can be used for solving other categories of location problems.